Indigenous Ways Infiltrating the Research Realm - Pascal, Sydney (Culture and Local Governance / Culture et gouvernance locale, 2023)
The summer of 2021 was the beginning of my experience as a researcher from Emily Carr University of Art & Design on a project that connected me with other researchers across Canada. The project was titled Research in Residence: Arts’ Civic Impact, and was an initiative in collaboration with Mass Culture, the Canada Council for the Arts, the Culture Statistics Working Group, the Ontario Trillium Foundation, and the Toronto Arts Foundation. Each researcher had their own area of interest, with my focus being on researching and exploring the innovative ways of reframing research methods and connecting with communities in the arts sector and academic institutions to align with methods derived from an Indigenous way of gathering information.